A Pilot Study of Simulation Training in Difficult Bag Mask Ventilation Using a Computerized Patient Simulator. (March 2019) - Pastis, Nicholas J; Tobin, Catherine D; Wolf, Bethany J; Reves, Jerry G; Schaefer, John J
Objective: Bag mask ventilation (BMV) is fundamental to airway management. Simulation is effective in airway management training, but its effectiveness for difficult BMV training is less clear. We evaluated the difference between type of training (simulation vs on patients) and the pass rate on a post-test on patients. Design: A single center pilot study was performed with 32 medical students randomized to participate in difficult BMV training on simulators or patients. Pre- and post-training tests on the simulator and on patients were recorded. Surveys of trainee confidence level were collected. The primary goal was to estimate the difference between type of training (simulation vs on patients) and the pass rate on the post-test on patients with an improvement of 10% or more in passing rate considered as a meaningful improvement. Secondary outcomes included whether or not participants passed the simulator post-test, post-test on patient confidence, and pre- and post-test confidence. Measurements and main results: Participants trained on the simulator had 13% higher passing rate on the post-test on patients compared to participants trained on patients (88% vs 75%). In addition, subjects that passed the simulator post-test had 11 times the odds of passing a post-test on patients relative to subjects that did not pass the simulator post-test ( P  = 0.023, odds ratio = 11.0, 95% confidence interval [CI] = 1.48-81.6). Post-training confidence levels were higher among those who passed the simulator pre-test and post-test and received simulator training. Conclusions: Simulation training for difficult BMV led to a higher passing rate on a post-test on patients compared to those trained on patients. This finding will need to be confirmed in larger randomized controlled trials. Successfully completing difficult BMV training on a simulator with a passing grade correlated with passing a test on difficult BMV on patients.